Temperature and Light Modulation of Herbicide Toxicity on Algal and Cyanobacterial Physiology - Gomes, Marcelo Pedrosa; Juneau, Philippe (Frontiers in Environmental Science, 2017)
HIGHLIGHTS We reviewed the interaction between light, temperature and herbicides on algal and cyanobacterial physiology. Temperature is the main factor affecting herbicide toxicity to algae and cyanobacteria. Changes in light environment may modulate the effects of photosynthesis-targeting herbicides. Important interactions between climatic parameters and herbicide toxicity have been discussed in the literature. As climate changes are expected to influence the growth conditions of aquatic photosynthetic organisms over the next century by modifying the physicochemical parameters of the environment (such as temperature and incident light characteristics), the following questions arise: How will variations in climatic conditions influence herbicide toxicity in algae and cyanobacteria? Are these coupled effects on aquatic photosynthetic organism physiology antagonistic, additive, or synergistic? We discuss here the physiological responses of algae and cyanobacteria to the combined effects of environmental changes (temperature and light) and herbicide exposure. Both temperature and light are proposed to influence herbicide toxicity through acclimation processes that are mainly related to cell size and photosynthesis. Algal and cyanobacterial responses to interactions between light, temperature, and herbicides are species-specific, making it difficult today to establish a single model of how climate changes will affect toxicity of herbicides. Acclimation processes could assure the maintenance of primary production but total biodiversity should decrease in communities exposed to herbicides under changing temperature and light conditions. The inclusion of considerations on the impacts of environmental changes on toxicity of herbicides in water quality guidelines directed toward protecting aquatic life is now urgently needed.